The Usage of Mycorrhizal Biofertilizer on 2 Varieties of Long Green Eggplant (Solanum melongena L.) in Dryland Soils - Iin Siti Aminah; Neni Marlina; Railia Karneta; Wuriesyliane Wuriesyliane; Kurnia Susanti; Diah Eka Puspita (Journal of Global Sustainable Agriculture, 2023)
Dryland soils a very high potential land for the development of agricultural crops, including vegetable crops, although the obstacles faced are due to low soil fertility, therefore efforts that can be made to increase production can use mycorrhizal biofertilizers and the use of high-yielding eggplant varieties. Hyphal elongation by mycorrhizal biofertilizer is expected to increase N, P, and K nutrient uptake, growth, and yield of green eggplant and green eggplant varieties can adapt well to less suitable environments. This research was conducted on a farmer's land on Klp Raya Road, Talang Kelapa, Alang-alang Lebar District, South Sumatra Province from March to June 2022. The research used field experiments.  The experimental design used RAK Factorial with 6 treatment combinations that were repeated 4 x.  Factor 1: Variety (V): Milano (V1), Ratih-Hijau-1 (V2).  Factor 2: Mycorrhizal Biofertiliser (M): 5 g (M1), 10 g (M2), 15 g (M3) per plant. The highest eggplant yield was achieved by the Milano variety with mycorrhizal biofertilizer 10 g/plant produce 10.14 kg/plot or equivalent to 27.04 tonnes/ha and increased 93.88% when compared to Ratih Hijau-1 variety with mycorrhizal biofertilizer 5 g/plant.